Pengabdian Kepada Masyarakat Pada Kelompok Pengepul Limbah Plastik Menjadi Cacahan Plastik Untuk Menciptakan Usaha Berdikari Dan Mandiri - Kamaluddin Lubis; Ninny A. Siregar; Nuril Mahda; Nela Permata Sari Lubis (Pelita Masyarakat, 2021)
Around our environment it is very easy to find plastic waste, in rivers and gutters this will have a negative impact because plastic waste is very difficult to decompose by the soil, it takes tens of years or even hundreds of years. Seeing this, the team through the Community Service (PKM) program was interested in using plastic waste as an effort to recycle waste to protect environmental damage. This PKM provides about how to chop plastic as an alternative effort in recycling waste from materials that are neglected by the community into product materials with high material value. it has a positive impact on promising plastics business community entrepreneurs. With the opening of these new business fields, the community can open new business fields and prevent the environment from polluting the soil, and the Go Green campaign